Motivações de permanência no trabalho voluntário: um estudo na fundação cidade viva João Pessoa-PB - Ageu, Joseilma Dantas (2015)
The subjects of the present research were active volunteers at Cidade Viva Foundation for over one year. This non-governmental organization is located in João Pessoa and it has over 350 volunteers; from where 122 subjects collaborated with this research, which aimed to reveal the motivations for staying or leaving the volunteer work. The adopted theoretical model was proposed by Cavalcante (2012), which allows tracing the volunteers’ motivational profile in certain given situations, such as staying or leaving the volunteer work. Data were obtained by questionnaire, during meetings that took place at the Foundation from July to August 2014. For data analysis, descriptive statistics (frequency, means, standard deviations, and coefficient of variation) and interferential statistics (Student t test for independent sampling and Bonferroni tests – ANOVA for multiple comparison/correlation sampling) were utilized. Thus, the research pointed that main motivations for staying at volunteer work at Cidade Viva Foundation are mainly settled in altruistic and learning profiles, which forward to the same conclusion from other studies in this area. Regarding the leaving process, it was noticed that questions related to religious nature are the ones that could lead them to withdraw this activity. As contribution, it is expected that such outcomes can help the Foundation to plan strategies that reduce/avoid members’ turnover, once each dropout represents loss for both the Foundation, which invests in the training of volunteers in their entry, and those ones who are taken care by actions from volunteering.